Fake Article Detection Application With Rabin Karp Algorithm - Harahap, Mawaddah; Marcel, Rico; Milatrisna, Dwi Yunita; Kuswulandari, Sri (Sinkron : jurnal dan penelitian teknik informatika, 2023)
Currently, fake (fake) information/articles are increasingly widespread. Surveys show that people receive fakes more than once a day. The most used channel for spreading fakes is social media. The fake phenomenon in Indonesia raises doubts about the information received and confuses the public. Artificial intelligence is an intelligent machine (computer), where a machine is trained in advance (machine learning) to solve certain problems. This artificial intelligence is expected to work faster and more accurately. There are several methods that can be implemented, one of which is using the Rabin-Karp algorithm. Where the reason for choosing the Rabin karp algorithm is that there is a process that can filter existing writing so that it is suitable for the problems discussed, namely article writing and an algorithm that can work at high speed so that users do not need a long time to receive predictive results for articles.